Frond Base Fracture and Oil Palm Production: Quantitative Evidence from Indonesia - Kurniadhi, Adhitya; Tejo Murti, Theofilus; Atmaka Aji , Wandha; Kristian Tinduh, Yulio; Kurniawan, Indra; Nurcahyono, Nurcahyono (Journal of Agriculture, 2025)
The frond base supports the oil palm tree trunk and distributes photosynthesis results. Frond base fracture (sengkleh) is thought to reduce plant growth performance and production. This study aims to quantitatively analyze the effect of frond base facture on vegetative and reproductive growth of oil palm. The study was conducted for three months at the KUD Sumber Sawit Makmur oil palm plantation, Central Kalimantan, Indonesia. The method used was an agronomic survey with observations on six plant blocks: three blocks with healthy trees and three with unhealthy trees (there were more than three sengkleh fronds). Three plant samples were observed in each block. The parameters observed included the number of frond bases facture, new frond growth, number of female flowers, number of bunches harvested, and average bunch weight. Data were analyzed using two-factor ANOVA and continued with a 5% DMRT test if there was a significant difference. The results showed that frond base conditions had a very significant effect on all observation parameters. Plants with normal frond bases showed faster new leaf sheath growth, more female flowers, and higher yields than plants with fractured frond bases. These findings confirm that frond bases can be used as important visual indicators in technical decision making in the field.